2015
DOI: 10.1111/jfd.12403
|View full text |Cite
|
Sign up to set email alerts
|

PCR‐based prevalence of a fatal reovirus of the blue crab, Callinectes sapidus (Rathbun) along the northern Atlantic coast of the USA

Abstract: There is a need for more information on the relationship between diseases and fluctuations of wild populations of marine animals. In the case of Callinectes sapidus reovirus 1 (CsRV1, also known as RLV), there is a lack of baseline information on range, prevalence and outbreaks, from which to develop an understanding of population‐level impacts. An RT‐qPCR assay was developed that is capable of detecting 10 copies of the CsRV1 genome. In collaboration with state, federal and academic partners, blue crabs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…In addition to the operational advantages of the closed system, recent studies have reported the occurrence of acute mortality in companies producing soft crab caused by a crab-specific reovirus (CsRV1) (Bowers et al 2010;Flowers et al 2016) and that the pathogenicity of this virus is related to high temperatures (Chung et al 2015). These findings would reinforce an additional advantage of closed production systems over open systems, due to greater possibility of control of environmental variables, including temperature, in this kind of system.…”
Section: Comparisons Between Productive Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the operational advantages of the closed system, recent studies have reported the occurrence of acute mortality in companies producing soft crab caused by a crab-specific reovirus (CsRV1) (Bowers et al 2010;Flowers et al 2016) and that the pathogenicity of this virus is related to high temperatures (Chung et al 2015). These findings would reinforce an additional advantage of closed production systems over open systems, due to greater possibility of control of environmental variables, including temperature, in this kind of system.…”
Section: Comparisons Between Productive Systemsmentioning
confidence: 99%
“…; Flowers et al . ) and that the pathogenicity of this virus is related to high temperatures (Chung et al . ).…”
Section: Soft‐shell Swimming Crab Farming Systemsmentioning
confidence: 99%
“…The quality and quantity of RNA was estimated on a Nanodrop spectrometer (FisherSci). The levels of CsRLV RNA present in the total RNA (=equivalent of 2.5 % of hemolymph) were assayed in triplicate using a one-step RT-qPCR assay with TaqMan® Fast Virus 1-Step Master Mix (Life Technologies) using the primers listed in Table 1 [11]. Standards for the CsRLV qPCR assay were prepared as described [12] ranging from 10 to 10 6 copies.…”
Section: A Reo-like Virus (Csrlv) Test Using Qpcr Assay 241 Hemocytesmentioning
confidence: 99%
“…In the blue crab, a reo-like virus (CsRLV) has been described that infects mesodermallyand ectodermally-derived tissues, especially hemocytes and epidermal tissues [10,11]. CsRLV is associated with the majority of mortality in captive molting crabs from shedding facilities, and CsRLV prevalence in wild intermolt crabs is reported to average 20% [12].…”
Section: Introductionmentioning
confidence: 99%
“…In native habitats, C. sapidus is subjected to a wide spectrum of parasitic pathogens, including viral, bacterial, and micro algal agents (Flowers et al, 2016;Shields, 2015 and literature cited). In invaded Mediterranean habitats, the occurrence of parasites in the species is to date virtually unexplored, even though it is an appreciat-ed shellfish product, in particular in Greece and Turkey (Mancinelli et al 2017c).…”
Section: Introductionmentioning
confidence: 99%